Directed Play Approach in Improving Early Literacy Skills of Children at RA An-Nisa Ternate City - Jelita Hi Usman; Irma Dewi Sartika; Radjiman Ismail; Rinelsa R Husain (Golden Ratio of Social Science and Education, 2026)
This study aims to describe the application of a directed play approach to improve early literacy skills in children at RA An-Nisa Kota Ternate. This study used a qualitative approach with a descriptive design. The research subjects included the students of RA An-Nisa, classroom teachers, and the head of RA. Data collection techniques were conducted through observation, interviews, and documentation. Data analysis was conducted descriptively and qualitatively through the stages of data reduction, data presentation, and drawing conclusions, with data validity ensured through source and technique triangulation. The results of the study indicate that the directed play approach is implemented through systematic lesson planning by integrating play activities with literacy goals, such as letter recognition, connecting sounds and symbols, enriching vocabulary, and expressing ideas orally. The implementation of this approach can increase children's engagement, motivation, and activity in early literacy learning. Children learn in a fun, stress-free environment that is appropriate for their developmental stages. Thus, the guided play approach has proven effective in improving early literacy skills in young children and is relevant for implementation in learning at RA institutions.